Physicochemical Conditions and Microbial Activities in the Highly Alkaline Gut of the Humus-Feeding Larva of Pachnoda ephippiata (Coleoptera: Scarabaeidae) - Lemke, Thorsten (American Society for Microbiology, 2003)
The soil macrofauna plays an important role in the carbon and nitrogen cycle of terrestrial ecosystems. In order to gain more insight into the role of the intestinal microbiota in transformation and mineralization of organic matter during gut passage, we characterized the physicochemical conditions, microbial activities, and community structure in the gut of our model organism, the humus-feeding larva of the cetoniid beetle Pachnoda ephippiata. Microsensor measurements revealed an extreme alkalinity in the midgut, with highest values (pH > 10) between the second and third crown of midgut ceca. Both midgut and hindgut were largely anoxic, but despite the high pH, the redox potential of the midgut content was surprisingly high even in the largest instar. However, reducing conditions prevailed in the hindgut paunch of all instars (E(h) ∼ −100 mV). Both gut compartments possessed a pronounced gut microbiota, with highest numbers in the hindgut, and microbial fermentation products were present in high concentrations. The stimulation of hindgut methanogenesis by exogenous electron donors, such as H(2), formate, and methanol, together with considerable concentrations of formate in midgut and hemolymph, suggests that midgut fermentations are coupled to methanogenesis in the hindgut by an intercompartmental transfer of reducing equivalents via the hemolymph. The results of a cultivation-based enumeration of the major metabolic groups in midgut and hindgut, which yielded high titers of lactogenic, propionigenic, and acetogenic bacteria, are in good agreement not only with the accumulation of microbial fermentation products in the respective compartments but also with the results of a cultivation-independent characterization of the bacterial communities reported in the companion paper (M. Egert, B. Wagner, T. Lemke, A. Brune, and M. W. Friedrich, Appl. Environ. Microbiol. 69:6659-6668, 2003).